Between a double crisis: Precarization, extractivism and the futures of the commonist politics - Narita, Felipe Ziotti [UNESP] (Adam Mickiewicz University Poznan, 2020)
To celebrate the 10th anniversary of Praktyka Teoretyczna journal, we have invited our long-lasting collaborators and comrades to reflect once again on the concept of the common and it’s possible futures by posing following questions: a) what is the most important aspect of the current struggles for the common?; b) what are the biggest challenges for the commonist politics of the future?; and c) where in the ongoing struggles do you see a potential for scaling-up and spreading the organisation based on the common? In his re-ply, Felipe Ziotti Narita situates his answer in the context of contemporary double capitalist crisis, which renders visible the commons as crucial for satisfying collective needs and purposes.
Keywords: Double capitalist crisis; Extractivism; Precarization; Reproduction; The commons